Edukasi Vitamin D pada pasien asma dalam upaya pencegahan kekambuhan asma di wilayah Puskesmas Olak Kemang Kota Jambi - Sitanggang, Fardiah Tilawati; Sakdiah, Siti; Simanjuntak, James P (Poltekkes Kemenkes Jambi, 2023)
Asthma is a chronic inflammation of the airways characterized by recurrent wheezing, coughing and tightness in the chest, especially at night due to airway obstruction. Asthma increases with air quality and changes in lifestyle. The severity of asthma is influenced by vitamin D, which plays a role in increasing the immune response (immunomodulator) and reducing inflammation in the lungs. Research by Simanjuntak et al in 2022 shows that vitamin D deficiency is strongly correlated with asthma and the severity of asthma. The prevalence of asthma in Jambi City is 1.7% with a recurrence of 62% and is the highest cause of death in Jambi City. Olak Kemang Health Center, Jambi City is one of the health centers that has a high number of asthma patients, namely 95 people with a low level of knowledge regarding vitamin D and asthma. After providing education regarding vitamin D and asthma, there was a significant change, namely an increase in knowledge which was visible from the pre and post tests. The involvement of government officials such as community health center officers and cadres plays a significant role in motivating asthma patients to take part in educational activities.